2023
DOI: 10.1038/s41598-023-38227-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraparotid lymph node metastasis affects distant metastasis in parotid adenoid cystic carcinoma

Abstract: To evaluate the relationship between factors of metastatic intraparotid lymph node (IPLN) and distant metastasis in parotid adenoid cystic carcinoma (ACC). Patients with surgically treated parotid ACC were retrospectively enrolled, and primary outcome variable was distant metastasis free survival (DMFS). The effect of factors of metastatic IPLN on DMFS was evaluated using Cox model. In total, 232 patients were included. Extranodal extension of IPLN and cervical lymph nodes did not impact the DMFS, and the 7th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, the authors failed to find an association between ENE and distant metastasis, the risk of which was significantly increased in solid cancers by ENE. Our previous study assessed the predictors of DMFS in 232 patients with adenoid cystic carcinoma and reported that ENE in neither the cervical nor the intraparotid LN affected DMFS [ 7 ]. The current study is a further supplement, confirming that ENE did not compromise survival, irrespective of LN location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the authors failed to find an association between ENE and distant metastasis, the risk of which was significantly increased in solid cancers by ENE. Our previous study assessed the predictors of DMFS in 232 patients with adenoid cystic carcinoma and reported that ENE in neither the cervical nor the intraparotid LN affected DMFS [ 7 ]. The current study is a further supplement, confirming that ENE did not compromise survival, irrespective of LN location.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of two or more positive LNs predicted significantly decreased disease control and increased death risk. Our previous study showed that intraparotid LN metastasis was significantly associated with inferior prognosis; however, the impact was not apparent until there were at least two metastatic intraparotid LNs in parotid adenoid cystic carcinoma [ 7 ]. These three studies combined with ours suggest that the impact of the intraparotid LN metastasis burden should be emphasized in the evaluation of LN status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation